Synergism Analysis of Bedding Slope with Piles and Anchor Cable Support under Sine Wave Vehicle Load - Li Dan-Feng; Wang Lian-Jun (Advances in Materials Science and Engineering)
Slope instability under dynamic load is the technical difficulty in the engineering; the evaluation of slope stability under dynamic load and the control of dynamic load is particularly important. In this paper, taking the right side slope of K27+140 m~380 m typical section (K27 slope for short) in Chongqing Fuling-Fengdu-Shizhu expresses highway as an example to calculate and analyze. The K27 slope is under sinusoidal vehicle load and supported by anchor cable and antislide pile to resist downslide strength; at the same time, the combined effect of them is studied. Three-dimensional finite element methodology (FEM) is used to simulate the bedding slope with piles and anchor cable support; furthermore, the eigenvalue can be obtained. In order to reduce error of the elastic boundary conditions caused by the reflection effect of wavelengths, the combination of Lysmer surface viscous boundary and traditional ground support boundaries is utilized to analyze and calculate the time-histories during bedding slope under dynamic load. The dynamic response of pile anchor support to resist sliding force is obtained. The concept of the pile anchor supporting coordinate interval is put forward. Furthermore, it is verified that the pile anchor supporting coordinate interval can be used to evaluate the stability of the slope under dynamic load and provide a new method for the control of the dynamic load.